Family Resources Management and Life Satisfaction of Elderly - Sulityowati, Asri; Krisnatuti, Diah (Journal of Family Sciences, 2018)
Elderly especially widower and widow must have done family resources management (FRM) in order to achieve satisfaction in life. This study was conducted to analyze the influence of family resource management on life satisfaction of elderly widower and widow. This study was using cross-sectional study with purposive for site selection in Timbulharjo Village, Sewon Subdistrict, Bantul, Yogyakarta Province. Total of 60 samples were gathered with a combination of simple random sampling and snow-ball techniques. The results of this study indicated atsocioeconomic status of the widower was higher in terms of average age and duration of education rather than widows, moreover the income of elderly widower greater than the widows. Non-foodexpenditure, stress management, and time management had a positive effect on the satisfaction of elderly life hence the more allocation on non-food expenditure, the better of stress management and time management could improve life satisfaction of the elderly. In addition, marital status associated and had a significant negative effect towards life satisfaction which mean that life satisfaction of elderly widower higher thanthe widow.